The effect of gap years on sense of purpose and career development - Kóré, Kinga (2021)
Gap year is an extended traveling experience when people explore pristine places and distant cultures often through not only travelling but volunteering or working. It allows them to take a break between life stages and contemplate their next step. The fundamental aim of this research was to better understand, via grounded theory formulation, how sense of purpose evolves in the context of gap years and its influence on career development. The research shows gap years positively affected participant's sense of purpose through identity work and sense making, which led to the more conscious and active development of their career path.